Transformative conflict mediation in multi-faith schools in South Africa - Maitumeleng Albertina Nthontho (Perspectives in Education, 2020)
Contradictions and contestations with regard to the implementation of religion policies have become a worldwide phenomenon. Research suggest an increasing number of costly and protracted court and legislative battles between schools and parents over religion in schools. In this article, I aim to highlight some of the conflicting issues that need to transformation while implementing the National Policy on Religion and Education of 2003 in some selected South African schools. Based on mediation theory, the study used individual interviews to gather data from twelve purposively selected school principals to investigate how they implemented the religion policy in their respective schools. The findings show that despite the implementation challenges of this policy, the majority of the school principals displayed the qualities of a transformative mediator by transforming conflicting religious interests of stakeholder groupings in their schools. I therefore recommend that universities should consider training school principals in the use of transformative mediation as a strategy to transform conflicts in schools as it holds potential benefits for fields such as education.